Kajian Etis Teologis Terhadap Remaja yang Melakukan Pernikahan Dini - Lumi, Altje; Kawengian, Elsadai Sofiana (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2023)
This research aims to provide a broader understanding of marriage which is a gift from God so that the phenomenon of early marriage among teenagers can be avoided. It should be noted that adolescents are the time when they go from childhood to adulthood so guidance from parents is also needed, because parents are the teachers in a child's life so that he can understand what should be done. The author uses research and qualitative approaches to produce data in the form of written or spoken words from people and observable behaviors. In collecting data, the author also conducted an interview technique with questions that had been prepared in order to get their own opinions from the respondents. The author conducts observations, to observe important matters related to the subject of the research or observations about the circumstances that occur at the research site.